2021
DOI: 10.3390/cancers13133143
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Precision Prevention Materials to Improve Primary and Secondary Melanoma Prevention Activities among Individuals with Limited Melanoma Risk Phenotypes

Abstract: Inherited variation at MC1R is associated with elevated melanoma risk among non-Hispanic whites (NHWs). MC1R genetic testing may unmask previously unrecognized disease risk, especially among individuals with few melanoma phenotypic risk factors. We recruited NHW individuals with limited phenotypic risk factors from two primary care clinics in west-central Florida. Participants (n = 1134) were randomized within MC1R genotype risk group (average/higher) to receive mailed precision prevention (i.e., intervention)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Non-genetics health professionals could be trained to offer testing and deliver results to assist in managing the volume and scale required for population-level testing. In two randomized controlled trials in primary care settings in the US, intervention arm participants were posted hardcopy booklets presenting their personal melanoma genomic risk information and educational information on prevention and early detection, followed by a phone call by a trained researcher or health educator (as opposed to a genetic counselor) [ 35 , 36 ]. Participant satisfaction with these study processes was high overall.…”
Section: Discussionmentioning
confidence: 99%
“…Non-genetics health professionals could be trained to offer testing and deliver results to assist in managing the volume and scale required for population-level testing. In two randomized controlled trials in primary care settings in the US, intervention arm participants were posted hardcopy booklets presenting their personal melanoma genomic risk information and educational information on prevention and early detection, followed by a phone call by a trained researcher or health educator (as opposed to a genetic counselor) [ 35 , 36 ]. Participant satisfaction with these study processes was high overall.…”
Section: Discussionmentioning
confidence: 99%
“…[22,37] In these studies and others, the provision of MC1R and similar melanoma genetic risk test results lead to behavioral activation but not worry and promote increased use of sun protection and skin screening, as well as reductions in sunburn in individuals who received the feedback. Further, individuals who receive average risk feedback do not increase risk behaviors such as tanning [38][39][40]. Current genetic testing technology allows for lowcost comprehensive genomic assessment, and MC1R is often 1.00 (0.00) Afraid [1][2][3][4][5][6][7] 1.50 (1.10) Hopeful [1][2][3][4][5][6][7] 4.63 (2.36) Confused [1][2][3][4][5][6][7] 1.94 (1.61) Determined to change [1][2][3][4][5][6][7] 4.38 (2.53) Distress, Sum 8.81 (2.23) evaluated as part of direct-to-consumer genetic tests.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies predominately recruited participants from two non-specialty, academic clinic settings in Tampa, Florida, U.S.A. Details of these studies have been published elsewhere (Lacson et al, 2021 , 2022 ). Trial participants who previously (i) consented to be re-contacted for future studies, (ii) provided an email address, (iii) completed the baseline study questionnaire for the intervention trial, (iv) indicated English as a language preference, and were (iv) less than 89 years of age and (v) not under active trial follow up were sent an email inviting them to participate in a COVID-19 research study.…”
Section: Methodsmentioning
confidence: 99%